Microvascular Dynamics and Hemodialysis Response of Patients With End-Stage Renal Disease - Lee, Jen-Shih; Lee, Lian-Pin (Frontiers in Bioengineering and Biotechnology, 2022)
In our previous analysis of three sets of hemodialysis studies, we found that patients possessing higher hematocrit have a higher filtration coefficient KSo and more fluid being restituted from the tissue. A new dynamic analysis is developed to reveal how the plasma protein concentration, restitution volume, and plasma volume are changing over the time course of 240 min hemodialysis. For patients with the filtration coefficient KSo as 0.43 or 5.88 ml/min/mmHg, we find that the restitution rate would reach 50% of the extraction rate in 5.3 or 57.4 min, respectively. By the end of hemodialysis, the restitution rate of both patients asymptotically approaches a value of 0.93 ml/min which is slightly higher than the extraction rate of 9.03 ml/min. The plasma volume drops by 10% of the total plasma volume in 11 min for patients with low KSo and drops by 2.1% and turns around to an increasing trend in 5.6 min for patients with high KSo. These results suggest that the filtration coefficient acts like a facilitator in restituting more fluid from the tissue to compensate for the loss of plasma volume due to extraction. The hematocrit data of three sets of hemodialysis also indicate that significant microvascular blood volume is shifted from small veins toward the venous side of macrocirculation. A better understanding of how the factors examined here cause hypovolemia can be the basis for one to modify the hemodialysis process such that the development of hypovolemia can be avoided over the course of hemodialysis.